Direct Microstructure Tailoring of Hard Carbon Electrodes for Fabrication of Dual-Carbon Potassium-Ion Hybrid Supercapacitors - Kim, Kangseok; Park, Jongyoon; Lee, Jiyun; Lim, Eunho; Hwang, Jongkook (Energy and Fuels, 2024)
The microstructure of hard carbon, including interlayer spacing, the degree of graphitization, and doped heteroatoms, has a significant impact on the K+ storage capability of hard carbon anodes in potassium-ion hybrid supercapacitors (PIHCs). However, previously reported microstructural engineering methods typically involve complex, time-consuming, and expensive multistep processes. Herein, we report the simple pyrolysis-guided microstructural engineering of hard carbon materials using cost-effective coffee waste (CW) as a recycled single carbon source for the fabrication of PIHC devices. For battery-type anodes, the direct pyrolysis of CW at various temperatures (700, 900, and 1100 °C) is conducted to control the microstructures and K+ storage behavior of hard carbon anode materials. Carbon prepared at 700 °C exhibits high specific capacity, large capacitive K+ storage contribution, and rapid K+ storage kinetics as a result of abundant surface defects and functional groups as well as a wide interlayer spacing. For capacitor-type cathodes, high surface area activated carbon is prepared using an industrially available KOH activation method. The optimized PIHC full cell exhibits a high energy density of 120 Wh kg-1, a power density of 3378 W kg-1, and a capacity retention of 83.6% after 3000 cycles at 0.5 A g-1, comparable to carbon materials synthesized by complex multistep processes. These findings indicate that simple microstructural engineering via pyrolysis is sufficient for fabricating dual-carbon PIHCs with an adequate electrochemical performance.
Keywords: Carbon electrode; Carbon material; Hard carbon; Hybrid supercapacitors; Interlayer spacings; Microstructural engineering; Microstructure tailoring; Multistep process; Potassium ions; Simple++